Kyrgyz Republic : Country Fiduciary Assessment Update 2007 - World Bank (Washington, DC, 2012)
This fiduciary assessment makes recommendations to strengthen public financial management in the Kyrgyz Republic, including procurement. This report takes stock of developments since 2002 within the Public Financial Management (PFM) Framework. It identifies the recommendations that have been implemented, and it lays out a road map to implement remaining reforms. It provides a basis upon which the Government of the Kyrgyz Republic (GOK) can formulate a capacity-building plan to improve its fiduciary system. Donors can use the results of this update in two ways: first, to develop strategies for assisting the capacity development plan; and second, to mitigate risks in individual operations. The country can use the information to monitor its fiduciary systems and the extent to which ongoing reform initiatives are improving performance. This assessment was prepared in close collaboration with government counterpart teams and other donors. The teams analyzed relevant pieces of legislation, gathered feedback through workshops, and conducted interviews with the Government, the private sector, and civil society. The report incorporates comments on earlier drafts and suggestions received from the government, including the Ministry of Finance (MOF), the Chamber of Accounts (COA), Ministry of Economic Development and Trade and the State Agency on Public Procurement and Materials Reserve (SAPPMR).